2007
DOI: 10.1016/j.jcrs.2006.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing refractive outcomes after combined phacoemulsification and pars plana vitrectomy

Abstract: The combined surgery included a small biometric error that was within the tolerable range in most cases. However, myopic shifts developed in patients with long axial lengths, poor preoperative visual acuity, and the preoperative presence of foveal detachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 24 publications
1
68
1
3
Order By: Relevance
“…observed a myopic shift of −0.5D in phacovitrectomy with gas tamponade relative to phacovitrectomy without gas tamponade [15] although other studies have not observed this association [8] [9]. In our own series there was no correlation between gas tamponade and increasing myopic shift on multivariate analysis.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…observed a myopic shift of −0.5D in phacovitrectomy with gas tamponade relative to phacovitrectomy without gas tamponade [15] although other studies have not observed this association [8] [9]. In our own series there was no correlation between gas tamponade and increasing myopic shift on multivariate analysis.…”
Section: Discussioncontrasting
confidence: 58%
“…Several groups have reported a myopic shift after phacovitrectomy for macula holes and ERM's, particularly with ultrasound biometry [3]- [8]. Optical biometry is now the gold-standard in pre-operative cataract assessment and may be less prone to myopic shift in phacovitrectomy [9], but there is conflicting evidence [10] [11] and the published literature remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The combined procedure is more time-consuming and technically a slightly more challenging procedure, but reduces costs and offers quicker visual rehabilitation by avoiding the need for additional surgery and allowing a single recovery period. [4][5][6] The aphakic state during surgery also gives excellent visibility and ensures unimpeded view for treatment of peripheral pathology.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,7,8,22,23 Previous authors have suggested that aiming for residual hyperopia, using Haigis formula for biometric calculation 9 or using individualised surgeon's A-constant may help to counteract the myopic shift.…”
mentioning
confidence: 99%
“…Jeoung и соавт. [16] сообщили результаты про-спективного исследования пациентов после витрэк-томии в сочетании с экстракцией катаракты. Усиле-ние рефракции сопровождалось увеличением пе-реднезадней оси, вероятность которого возрастала в так называемых длинных глазах с длиной оси более 24,5 мм.…”
unclassified